2013
DOI: 10.1155/2013/481264
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Red Blood Cell Distribution Width in Patients with Cardiac Syndrome X

Abstract: Abstract. BACKGROUND: Cardiac syndrome X (CSX) is a condition characterized by chest pain with normal coronary arteries. However, its pathogenesis has not fully been understood yet. Red blood cell distribution width (RDW) has recently been suggested as a marker of acute and chronic cardiovascular diseases, while no data is available in patients with CSX. METHODS: One hundred and twenty consecutive patients with CSX and 102 normal controls were prospectively enrolled in this study. Blood samples were drawn from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
0
5
0
2
Order By: Relevance
“…A retrospective analysis was conducted in patients with primary diagnosed, pathologically confirmed, and sporadic RCC and controls identified hospital patients with simple renal cyst, between January 2010 and June 2013 at Department of Urology at Peking University Third Hospital. The exclusion criteria of the study were the presence of medical history of other malignancy, pregnancy, kidney transplantation, hematological disorders, severe anemia, infectious or inflammatory disease, iron supplementation therapy, recent venous thrombosis (past 6 months), recent blood transfusion (past 3 months), chronic obstructive pulmonary disease, hepatitis B or C, heart failure, arrhythmia, untreated thyroid disease, and severe liver and/or renal insufficiency as described previously [ 26 ]. All data on age, gender, body mass index (BMI), history of hypertension or diabetes, smoking, blood parameters, histology, stage at diagnosis (2009 AJCC TNM classification), and Fuhrman grading were obtained from electronic records and medical charts.…”
Section: Methodsmentioning
confidence: 99%
“…A retrospective analysis was conducted in patients with primary diagnosed, pathologically confirmed, and sporadic RCC and controls identified hospital patients with simple renal cyst, between January 2010 and June 2013 at Department of Urology at Peking University Third Hospital. The exclusion criteria of the study were the presence of medical history of other malignancy, pregnancy, kidney transplantation, hematological disorders, severe anemia, infectious or inflammatory disease, iron supplementation therapy, recent venous thrombosis (past 6 months), recent blood transfusion (past 3 months), chronic obstructive pulmonary disease, hepatitis B or C, heart failure, arrhythmia, untreated thyroid disease, and severe liver and/or renal insufficiency as described previously [ 26 ]. All data on age, gender, body mass index (BMI), history of hypertension or diabetes, smoking, blood parameters, histology, stage at diagnosis (2009 AJCC TNM classification), and Fuhrman grading were obtained from electronic records and medical charts.…”
Section: Methodsmentioning
confidence: 99%
“…In a study in patients with cardiac syndrome X, CRP level was found to be correlated with the activity of the disease [ 14 ]. In a similar vein, elevated red cell distribution width (RDW) levels were found to be independently associated with presence of CSX, and in the same study RDW and CRP levels were reported to correlate positively [ 15 ]. In another study, the presence of endothelial dysfunction and sub-angiographic atheroma was revealed in patients with CSX [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Çalışmaya Mersin Üniversitesi Tıbbi Onkoloji Kliniği'ne başvuran, dosyasına ulaşılabilen tüm metastatik kolorektal kanserli hastalar alındı. Çalışmanın dışlama kriterleri; başka bir malignite öyküsü olması, gebelik, böbrek nakli, hematolojik hastalıklar, ciddi anemi, enfeksiyon veya inflamatuar hastalıklar, demir eksikliği tedavisi, yeni venöz tromboz (son 6 ayda), yeni kan transfüzyonu (son 3 ayda), kronik obstrüktif akciğer hastalığı, hepatit b veya c, kalp yetmezliği, aritmi, tedavi edilmemiş tiroid hastalığı ve bilinen ciddi karaciğer ve/veya böbrek hastalığı olması (17) . İnflamasyonun, solid tümörlerin progresyonunda rol oynadığı gösterilmiştir, ancak agresif hastalığın artmış inflamasyona neden olup olmadığı veya inflamasyonun agresif hastalıktan kaynaklanıp kaynaklanmadığı belirsizdir.…”
Section: Yöntemunclassified